Hematological Toxicity During Concomitant Treatment With Ruxolitinib and Avelumab for Merkel Cell Carcinoma - Buonerba, Luciana; Di Trolio, Rossella; Grimaldi, Antonio; Tucci, Aniello; Leo, Emilio; Ingenito, Concetta; Costabile, Ferdinando; Ragone, Gianluca; Savastano, Beatrice; Uzzauto, Maria Teresa; Belsito Petrizzi, Valeria; Di Lorenzo, Giuseppe (Frontiers in Oncology, 2020)
Background: Merkel cell carcinoma (MCC) is a rare neuroendocrine skin cancer. It frequently emerges in the presence of immunosuppression states such as myeloproliferative syndrome (MS). MS is treated with ruxolitinib, a selective JAK1 and JAK2 inhibitor. Avelumab, an anti PDL-1 inhibitor, is the standard treatment for MCC. To date it is unknown if avelumab and ruxolitinib have a synergistic or antagonistic effect when used together. Methods: We have identified all patients diagnosed with MCC, treated with avelumab, concomitant ruxolitinib, belonging to Tortora Hospital, Pagani and Santa Maria La Pietà Hospital, Nola, Italy between June 1 2019 and April 1 2020. Results: Among six MCC patients, we have found two patients in treatment with concomitant drugs. Both patients were being treated with ruxolitinib for MS as a standard regimen without suffering any hematological side effects. After starting doses of avelumab, we found thrombocytopenia, leukopenia, and anemia after cycle 1 and cycle 4, respectively, and decided to suspend both treatments. Following the suspension, the hematological values improved allowing us to restart treatment with avelumab without the need to resume ruxolitinib treatment. Conclusions: The combined treatment of ruxolitinib and avelumab demonstrated severe toxicity. Modifying the schedule or reducing the dose of both drugs needs to be studied in order to be able to treat both pathologies.